2021
DOI: 10.22146/jtbb.66391
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Mudskipper Fish (<i>Periophthalmus</i> spp.) from Baros Beach, Bantul, Yogyakarta

Abstract: Mudskipper fish is amphibious fish belonging to the family Gobiidae. Coastal communities widely consume mudskipper to meet their animal protein needs. Mudskipper is primarily cryptic species that are morphologically difficult to identify and distinguish from other mudskipper fish species. Consequently, it can be confused with the naming of mudskipper fish species and can affect the conservation efforts of the fish in their habitat. One of the molecular approaches that can be used to identify the fish species q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The samples were preserved in 99 % ethanol and kept at −20 °C for later analysis. To broaden our analysis, we incorporated an additional 38 previously documented COI sequences of common mudskippers from various locations on the south coast of Java, including Bogowonto Lagoon, 23 Baros Beach, 24 and Pasir Mendit Beach 25 ( Table 1 ). Therefore, the total population in this study consisted of five distinct populations ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were preserved in 99 % ethanol and kept at −20 °C for later analysis. To broaden our analysis, we incorporated an additional 38 previously documented COI sequences of common mudskippers from various locations on the south coast of Java, including Bogowonto Lagoon, 23 Baros Beach, 24 and Pasir Mendit Beach 25 ( Table 1 ). Therefore, the total population in this study consisted of five distinct populations ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…These mangroves thrive along the interior coastlines of Indonesia's large islands and estuaries, 22 providing a unique habitat for mudskippers. Previous DNA barcoding studies have explored mudskipper species in various mangrove and estuary regions of Indonesia, such as Bogowonto Lagoon, 23 Baros Beach, 24 Pasir Mendit Beach, 25 Tekolok Estuary, 26 and several sites in Java and Bali. 27 These studies mainly focused on the southern coast of Java, which features mangrove forests along its inner coastlines, bordering the Indian Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the region in animals is adequately conserved among species, but also sufficiently variable between species to permit dependable taxonomic identification (Bingpeng et al 2018;Pentinsaari et al 2016). In Indonesia, DNA barcoding with COI mitochondrial gene has been used to identify freshwater and marine fish species (Dahruddin et al 2016;Fadli et al 2020;Aji and Arisuryanti 2021;Rhaifa et al 2021;). A hybrid technique of genetic and morphological characteristics has been widely employed and verified for the taxonomic categorization of various fish species, with special emphasis on Gobiiformes (Islam et al 2021;Kovačić et al 2022;Thacker et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, adaptations in morphological, physiological and behavioral traits allow them to move between aquatic and terrestrial habitats (Radkhah and Eagderi, 2019). The mudskipper amphibian lifestyle is aided by morphological and physiological adaptations such as aerial vision and smell, increased ammonia tolerance, locomotion of pectoral fins for walking on land, and increased immunological protection against pathogens (Aji and Arisuryanti, 2021). Mudskipper type Periopthalmus waltoni has the ability to absorb heavy metals and then degrade them into environmentally friendly materials (…”
Section: Introductionmentioning
confidence: 99%